Diagnostic accuracy of B type natriuretic peptide and amino terminal proBNP in the emergency diagnosis of heart failure. Issue 5 (14th April 2005) - Mueller, T; Gegenhuber, A; Poelz, W; Haltmayer, M
Abstract : Objective: To compare head to head the diagnostic accuracy of B type natriuretic peptide (BNP) and the amino terminal fragment of its precursor hormone (NT-proBNP) for congestive heart failure (CHF) in an emergency setting. Methods: 251 consecutive patients presenting to the emergency department with dyspnoea as a chief complaint were prospectively studied. Patients with acute coronary syndromes were excluded. The diagnosis of CHF was based on the Framingham score for CHF plus echocardiographic evidence of systolic or diastolic dysfunction. Blood concentrations of BNP and NT-proBNP were measured by two commercially available assays (Abbott and Roche methods). The diagnostic accuracies of BNP and NT-proBNP were assessed by receiver operating characteristic curve analysis. Results: Areas under the curve for BNP and NT-proBNP in patients with dyspnoea caused by CHF (n = 137) and in patients with dyspnoea attributable to other reasons (n = 114) did not differ significantly (area under the curve 0.916 v 0.903, p = 0.277, statistical power 94%). Cut off concentrations with the highest diagnostic accuracy were 295 ng/l for BNP (sensitivity 80%, specificity 86%, diagnostic accuracy 83%) and 825 ng/l for NT-proBNP (sensitivity 87%, specificity 81%, diagnostic accuracy 84%). Evaluation of discordant false classifications at these cut off concentrations showed no advantage for either BNP nor NT-proBNP in the biochemical diagnosis of CHF (17 misclassifications by BNP and 14 by NT-proBNP, p = 0.720). In the population studied, age, sex, and renal function had no impact on the diagnostic utility of both tests when compared by logistic regression models. Conclusions: BNP and NT-proBNP may be equally useful as an aid in the diagnosis of CHF in short of breath patients presenting to the emergency department.